A Catheter‐Deployable Soft Robotic Inflatable Basket for Enhanced Conformability to the Left Atrium of the Heart. Issue 4 (16th January 2020) - Farokhnia, Nazanin; Caprio, Alexandre; Kashyap, Varun; Al'Aref, Subhi; Baskaran, Lohendran; Mosadegh, Bobak; Dunham, Simon
Abstract: This paper presents the design, fabrication, and test results for a novel basket catheter that utilizes soft robotic technology, which can conform to complex patient anatomy. Two designs of basket‐shaped balloons in three sizes are fabricated based on a CO2 laser cutting method from thin (<50 µm) thermoplastic polyurethane. The balloons are deployed in four soft‐material 3D printed left atria, whose geometries are based on volume rendered segmentation of cardiac computed tomography (CT) scans. The coverage and conformability to the realistic patient anatomies is tracked with the small patches of pH paper that indicate, via a color change, contact with a basic solution that lined the 3D printed atriums. The conformability of these inflatable basket catheters is demonstrated as high as (85%) for the optimized design. To visualize the balloon's performance, microCT images of balloons deployed in 3D printed models are shown. These images show the ability of the balloons to adapt to complex patient anatomy and do not exhibit any spline bunching or other deleterious mechanical behavior. This platform has the potential to be coupled with electrical sensors for simultaneous multisensor mapping of atrial fibrillation and other cardiac arrhythmias. Abstract : Soft robotic designs for basket catheters are developed and their conformability is assessed in patient specific 3D print models segmented from human cardiac computed tomography images. The results show improved conformability when compared to the reported performance for conventional basket catheters. Furthermore, the designs show more reliable mechanical actuation than typical basket catheters, where individual splines often bunch.